Q: What is the 4 to 1 rule for ladder?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

1, 4, 9, 16, ......., (n squared),

There are infinitely many possible answers: Rule I: Output = 4 (whatever the input, the output is 4). Rule 2: Output = Input - 2 Rule 3: Output = Input/2 + 1 Rule 4: Output = (Input/3)2

There are infinitely many possible answers. Rule 1: Add 9 to Input Rule 2: Add 5 to 2*Input Rule 3: Add 1 to 3*Input Rule 4: Subtract -3 from 4*Input or, moving away from whole numbers, Add 3.8 to 2.3 times Input.

Multiply each preceding term by 4.

93

Related questions

1:1 1:2 1:3 1:4

1/4 the height of the ladder. (flat top on rungs should be level when ladder is placed right.

That probably refers to the ratio between the length of the ladder, and the distance at which you place the bottom part of the ladder from the wall. If this distance is too short, you have the risk of the ladder falling backwards.

2 squared 1 = 4 so the divisibility rule is that it is divisible by 1, 2 and 4.

The rule is multiply the previous term by -1 to find the next term.

The Ascent of Man - 1973 The Ladder of Creation 1-9 was released on: UK: 1973 USA: 4 March 1975

what are 4 bases that make up the rungs of the DNA ladder

Each number is -4 times the previous one. That means that you can write a recursive rule as: f(1) = -3 f(n) = -4 * f(n-1) The explicit rule involves powers of -4; you can write it as: f(n) = -3 * (-4)^(n-1)

1 i think other people feel free to change this

The slope is 4 (no units), and the ladder is 16.492 feet long. (rounded)

x^2=(x-4)^2+y^2 height up the wall = y = (x^2-(x-4)^2)^1/2 so if the length of the ladder is 10 feet Y= (100-36)^1/2 = 8

Each number is -4 times the previous one. That means that you can write a recursive rule as: f(1) = -3 f(n) = -4 * f(n-1) The explicit rule involves powers of -4; you can write it as: f(n) = -3 * (-4)^(n-1)